Kajian Karakteristik Arsitektur Karya Tan Tjiang Ay Studi Kasus - Andrey Caesar Effendi; Danang Harito Wibowo (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2018)
Many media has published Tan Tjiang Ay’s works. But not many have examined the style or philosophy of design from the Tan Tjiang Ay deeply. This study became interesting, because Tan Tjiang Ay's design style resembled the style of modern architectural design, even though he never mentioned it by himself. Therefore, the researcher explored the characteristics of the architectural design of the house by Tan Tjiang Ay. This research method is qualitative approach, by conducting literature studies, field studies, and architectural analysis by using several examples of residential designs by Tan Tjiang Ay to get comprehensive conclusion. The results of the study indicate that the architectural characteristics of residential houses by Tan Tjiang Ay in Bandung are Modern Architecture style.